Multiple Reoccupations after Four Paleotsunami Inundations (0.3–1.3 ka) at a Prehistoric Site in the Netarts Littoral Cell, Northern Oregon Coast, USA. Issue 2 (18th November 2016) - Minor, Rick; Peterson, Curt D.
Abstract : Netarts Bay is the setting of one of the largest concentrations of late prehistoric Native American settlements on the tectonically active Oregon coast. A prehistoric site (35TI74) exposed by sea cliff erosion in 1998 at the south end of the Netarts littoral cell contained a stratigraphic record of activity by prehistoric Native Americans and interbedded paleotsunami deposits. The nearfield paleotsunamis were produced by great Cascadia earthquakes (Mw8.5 ± 0.5) emanating from the Cascadia Subduction Zone offshore, as previously documented in episodically buried tidal marsh surfaces at the south end of Netarts Bay and in many other estuaries in the region. The cultural deposits at 35TI74 reflect multiple reoccupations by Native Americans at this barrage creek flood plain site between paleotsunami runup events (≥7.5 m elevation) at 1.3 ka, 1.1 ka, 0.8–0.9 ka, and 0.3 ka. The conditions that led to the exposure of 35TI74 are traced to erosion of a protective beach dune ramp at the south end of the Netarts littoral cell, placing the site within reach of progressive storm‐surf erosion. The diminishing geoarchaeological record at 35TI74 represents a microcosm of the sea cliff erosional processes that threaten vulnerable prehistoric shoreline archaeological sites along much of the Pacific Northwest Coast.